The genetic and phenotypic correlations between milk and reproductive traits in Holstein cows - Özçelik, M; Dogan, I (Scientific Technical Research Council Turkey, 1999)
In this study, the genetic and phenotypic correlations between milk production traits (milk yield, lactation duration, dry period) and reproductive traits (the number of inseminations per conception, service period, calving interval and gestation period) in Holstein Cows were investigated. The data relating to milk and reproductive traits in the period of 1985-1992 of a Holstein herd at the Bala State Farm was used. The genetic correlations were generally higher than phenotypic correlations between traits investigated in this study. In milk production traits, the phenotypic correlations between the milk yield and the lactation duration (0.41) and the dry period (-0.14) were statistically significant (P<0.001). In addition, a highly genetic correlation (-0.94) was found between the milk yield and the dry period. Among the reproductive traits investigated, the highest correlations were observed between the service period and the calving interval(0.93, P<0.001). The number of inseminations per conception was highly genetically correlated with the service period and the calving interval (0.83 and 0.56, respectively). Although negative genetic correlations ranging from -0.44 to -0.76 were found between the milk yield and the investigated reproductive traits, phenotypic correlations (except gestation period) were positive and statistically significant (P<0.01, P<0.001). Both the lactation duration and the dry period were highly genetically and phenotypically correlated with the service period and the calving interval.
Holştayn Irki İneklerde Süt ve Döl Verimi Özellikleri Arasindaki Genetik ve Fenotipik Korelasyonlar
Keywords: Holstein; correlation; milk yield; reproductive traits